Educação ambiental: propostas e desafios - Feitosa, Bruno Alves (Universidade Federal do Tocantins, 2019)
The present work whose theme is Environmental Education: proposals and challenges, has The main objective is to analyze the importance of environmental education at school, as well as in the bird village of Tocantinópolis - TO. Its about a qualitative research that will look at why the problem-issue, so they can be analyzed. The data collected were through questionnaire and observation. The adopted theoretical framework is based on: relationships of environmental education and rural education, and in one of the chapters, We sought to take a theoretical approach to the geographical concepts, space, territory and place. The investigation had an interventional character from action research, data are being collected through projects developed by teachers and also in institutional school documents as well as in general observations and through the questionnaire applied. The data obtained showed the great need to work on environmental education in the community as in school. The analyzes were performed from the observation of the daily life of school environment and by analyzing the questionnaires. Although the The results obtained were predominantly positive regarding environmental education, especially, much remains to be done, both at school as in the studied community.